ANALISIS STRATEGI BISNIS PERUSAHAAN ASURANSI KERUGIAN TERHADAP KUALITAS LAYANAN KLAIM BAGI PEMEGANG POLIS ASURANSI KENDARAAN BERMOTOR - Firdausi, Irawan; Purwoko, Bambang; Supriyadi, Edy (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2017)
The development of insurance industry in Indonesia is growing rapidly in the last decade as affected by the improving Indonesian economic conditions, especially in motor vehicle insurance product. These conditions encourage the majority of insurance companies to develop motor vehicles insurance product aggressively and innovatively. One of the crucial factors to be considered public in purchasing a motor vehicle insurance policy is the customer’s expectations for service quality of claim as consideration of the company's business strategy. In this quantitative descriptive study, the author divides the service expectations of claim in three main stages, namely claim acceptance, claim processing, and claim settlement. The aim of this study is to investigate the desired service and the adequate service of claim by the motor vehicle insurance policyholders as factors in the service expectations that affect the quality of service. The survey was conducted for two months, in October - December 2015 with a sample size of 230 people in incidental sampling method. The analytical method used in this research is Structural Equation Model (SEM). Results from this study indicate that the business strategy adopted by insurance companies and service expectations motor vehicle insurance policy holders in each stage of the claims process affect the services quality of claim significantly. Keywords: business strategy, motor vehicle insurance, desired service, adequate service, service expectations, service quality